Development of the talmudic Sugya by amoraic and post-amoraic amplification of a tannaitic Proto-Sugya - Hauptman, Judith 1943- (1987)
The discovery of the late date of composition of the stama, the anonymous passages which account for at least half of all Talmudic material, has led many redaction critics to suggest a two-source theory for the origin of the Babylonian sugya. According to this view, the generating matrix of the sugya was composed primarily of memrot 'amoraic dicta' and it was later expanded by anonymous redactors who interpolated much original commentary, as well as numerous beraitot. In this paper an alternative three-source theory is presented which posits that the oldest redacted stratum of the sugya was composed of tannaitic sources, mishnah, and related beraitot, rather than memrot. A second layer consisting of amoraic responses was subsequently added, with each memra inserted either before or after the relevant source of the tannaitic substratum. Finally, a third layer was added by the stama who wove the tannaitic and amoraic sources into a unified whole. After presenting several general proofs of this simple chronological model, a lengthy sugya in Kiddushin is analyzed to show how it makes the organizational principles of the sugya more easily accessible and on occasion suggests interpretations of passages which adhere more closely to the simple meaning of the words.